Barriers to the adoption of fuel cell vehicles: A qualitative investigation into early adopters attitudes. (January 2017) - Hardman, Scott; Shiu, Eric; Steinberger-Wilckens, Robert; Turrentine, Thomas
Abstract: Fuel Cell Vehicles (FCVs) are now approaching wider spread consumer adoption, with some of the largest OEMs having released or about to release commercial products. However, research into consumer perceptions of FCVs has been extremely limited to date. This paper investigates automotive early adopter attitudes toward FCVs by performing interviews with high-end BEV owners. This sample was chosen as based on a preceding study it was expected that these adopters would have a greater level of awareness and knowledge of FCVs compared to the general population. It was expected that this would lead to more insightful results. In this study 5 consumer barriers to FCV adoption emerge. These are; the lack of hydrogen infrastructure, the source of hydrogen, the inability of FCVs to be recharged from home, cost issues and also concerns about hydrogen safety. This paper goes on to make recommendations on how to solve these consumer barriers stating that; hydrogen infrastructure needs to be pre-developed, hydrogen should be sustainably generated, FCVs should have the ability to be partially charged at home, hydrogen fuel will need to be subsidised in the early market, vehicles need to be positioned in the correct markets, and safety concerns can be mitigated partly through education and outreach. Finally this paper finds that consumers do desire the range of a FCV and there is also consumer demand for FCVs ability to provide emergency back-up power.